Sports classification and athletes with intellectual disabilities: measuring health status using a questionnaire based on the international classification of functioning, disability and health - Tussis, L.; Lemmey, S.; Burns, J. (Adapted Physical Activity Quarterly, 2024)
Most people with intellectual disabilities have comorbid health conditions, which will impact optimization of sporting performance. Classification is used in Paralympic events to ensure that those with similar levels of functional ability compete fairly against each other. An evidence-based approach needs to be developed for athletes with intellectual disabilities to be classified in relation to their overall functional capacity into competition groups of similar ability. This research builds on previous work using the taxonomy of The International Classification of Functioning, Disability and Health (ICF) to group athletes with intellectual disabilities into comparable competition groups as an approach to Paralympic classification. Three groups of athletes—Virtus, Special Olympics, and Down syndrome—are compared using the ICF questionnaire indicating functional health status in relation to sporting performance. The questionnaire was found to discriminate between athletes with Down syndrome and other athletes, and an approach to using a cutoff score to develop competition classes is explored.